Zr‐Containing UiO‐66 Metal‐Organic Frameworks as Highly Selective Heterogeneous Acid Catalysts for the Direct Ketalization of Levulinic Acid. (17th January 2022) - Rapeyko, Anastasia; Rodenas, Miguel; Llabrés i Xamena, Francesc X.
Abstract: Zr‐containing UiO‐66 materials are active and reusable heterogeneous catalysts for the selective ketalization of levulinic acid (LA) with 1, 2‐propanediol, affording selectivities of up to 91–93% at full LA conversion, with very low levels of ester or ketal–ester byproducts. This allows the preparation of the target ketal directly from LA and avoiding intermediate esterification steps of LA to levulinate esters to minimize the formation of unwanted side products. The catalytic activity of UiO‐66 is found to depend critically on the hydration degree of the solid and the amount of missing linker defects. The most likely active sites for ketalization in (defective) UiO‐66 are Brønsted‐induced acid sites arising from the strong coordination and polarization of H2 O molecules onto accessible Zr 4+ associated with missing linker defects. A progressive deactivation is observed upon catalytic reuse, which is attributed to adsorbed reaction products poisoning the catalytic sites. These adsorbed products are easily removed by washing the spent catalyst with a dilute 2% HCl ethanolic solution, which completely restores the initial catalytic activity while maintaining the crystallinity of the solid intact. Abstract : Zr‐containing UiO‐66 is a highly selective and recyclable heterogeneous acid catalyst for the direct conversion of biomass‐derived levulinic acid (LA) into the corresponding ketal, with selectivities of up to 91–93% at full LA conversion and very low levels of ester or ketal–ester byproducts. Catalytic performance critically depends on the hydration degree of the solid and the amount of missing linker defects.